Development of gesture database for an adaptive gesture recognition system - Mohd Azri, Abd Aziz; Wan Khairunizam, Wan Ahmad; Siti Khadijah, Zaaba; Shahriman, Abu Bakar, Dr.; Nazrul Hamizi, Adnan; Rudzuan, Mohd Nor (IJENS Publishers, 2012)
Link to publisher's homepage http://www.ijens.org/